DISHARMORNISATION OF CRIMINAL LIABILITY RELATED TO LAND FIRE DUE TO CLEARING PLANTATION LAND - Arman Koedoeboen (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2020)
Burning forests or land is a crime that must be combated comprehensively by every party. One effort to punish perpetrators of forest or land burning is to impose a prison sentence and the maximum possible fine, to act as a deterrent and serve as a lesson to those who commit this act. The emergence of disharmonization between Law No. 32 of 2009 concerning Environmental Protection and Management and Law No. 39 of 2014 concerning Plantations regarding criminal sanctions against perpetrators of land burning is studied with the assumption that what is happening is the result of a malfunction of the law and related law enforcement. with land fires as expected. The type of research used is normative juridical legal research, namely research that focuses on examining the application of rules or norms in positive law. The existence of multiple interpretation articles has hampered the achievement of legal objectives, namely providing a sense of justice, legal certainty and legal benefits. This multi-interpretation article creates legal uncertainty due to the variety of judges' decisions on the same case. Law Number 32 of 2009 concerning Environmental Protection and Management and Law Number 39 of 2014 concerning Plantations are also less useful because they cause fear in the community, thereby triggering unrest in society. Commission I DPR RI needs to immediately revise or harmonize Law Number 32 of 2009 concerning Environmental Protection and Management and Law Number 39 of 2014 concerning Plantations, especially regarding restrictions or benchmarks for offenses and the application of criminal sanctions.